The concept of enhanced recovery after surgery in gynecological oncology - Yu.E. Dobrokhotova; Ter-Ovanesov M. D.; Borovkova E.I; Kukosh M. Yu; Zhelezkova T.A (LCC «Medicine-Inform», 2018)
The concept of enhanced recovery after surgery in gynecological oncology Dobrokhotova Yu.E.1, Ter-Ovanesov M. D.2, Borovkova E.I.1, Kukosh M. Yu.2, Zhelezkova T.A.1 1 Pirogov Russian National Research Medical University, Moscow 2 Peoples' Friendship University of Russia, Moscow The proven and widely recognized advantage of using the concept of Enhanced recovery after surgery (ERAS) is an enhanced postoperative recovery of patients due to the rational preoperative preparation, reducing surgical stress and the number of postoperative complications, which in total reduces the length of hospital stay and treatment costs. Currently, the results of several prospective randomized trials have convincingly proven the effectiveness of the ERAS in gynecological oncology. The basic ERAS protocol consists of 21 items and includes measures aimed at informing the patient, a full preoperative examination, elimination of pre-operative fasting, optimization of the volume of infusional therapy, absence of mechanical preparation of bowels, use of multimodal analgesia, prevention of nausea and vomiting, rational antibiotic- and thromboprophylaxis, a personalized approach to the use of drains and probes, prevention of intraoperative hypothermia, as well as early activation of patients and their fast discharge from the hospital. Key words: gynecological oncology, surgery, ERAS, fast-track surgery, enhanced postoperative rehabilitation, nutritional and perioperative support. For citation: Dobrokhotova Yu.E., Ter-Ovanesov M.D., Borovkova E.I. et al. The concept of enhanced recovery after surgery in gynecological oncology // RMJ. 2018. № 5(I). P. 45-50.